The GraphoGame Method: The Theoretical and Methodological Background of the Technology-Enhanced Learning Environment for Learning to Read by Ulla Richardson and Heikki Lyytinen - Richardson, Ulla; Lyytinen, Heikki (Human Technology, 2014)
This paper provides an overview of the GraphoGame method. Both theoretical and methodological aspects related to the method are presented. The method's guiding principles are based on the prevailing theories and experimental research findings on learning and teaching basic reading skills in alphabetic languages, especially from the point of view of a struggling reader. Because the nature of the target language and its relation to its writing system play central roles in the GraphoGame method, this approach requires the method to be flexible in order to be valid for learners of different languages and orthographies. Thus, the aim of the developed technology is to provide an appropriate reading support tool for all learners—from struggling learners to typical learners—in any language environment. We present an overview of results gained from GraphoGame intervention studies as well as challenges for the usability of the method.